The Gravity Signature of a Large Quaternary Depocentre off Southeastern Canada - Courtney, Robert; Piper, David (Géographie physique et Quaternaire, 1992)
ABSTRACTNew bathymetry, gravity and Pliocene - Quaternary sediment isopach maps have been compiled and gridded for the Scotian margin. A large positive gravity anomaly exists over the Laurentian Fan, which is the major Pliocene - Quaternary depocentre on the Scotian margin. This gravity anomaly is not related to deep structure but can be largely explained by considering the Pliocene-Quaternary sediments as isostatically uncompensated. This implies that the underlying continental margin lithosphère has had considerable strength for at least 3 Ma. Some residual anomalies not accounted for by Pliocene-Quaternary sediment thickness may represent thicker Miocene depocentres, but improved seismic and stratigraphie data are required to assess this possibility. The technique of gravity identification of major sediment depocentres is a useful reconnaissance tool in certain circumstances, such as where there is a topographic expression and the deposit is thick and of major areal extent.